Análise experimental de pilares de concreto armado, reforçados com concreto auto adensável e conectores - Ferreira, Diego Borja (2014)
Studying strengthening in reinforced concrete structures is an ever-growing necessity in civil construction. Flaws during design, execution, use, and maintenance, as well as the use of poor quality construction materials and a structure's functional change may all lead to this necessity. Strengthening a given structure is justified whenever it becomes necessary to increase its bearing capacity. The small number of studies which analyse the behaviour of strengthened structures makes it difficult to establish parameters that may contribute to designing such projects. This research assessed the behaviour of reinforced concrete columns under compression and one-way eccentricity, with an initial section of 120 mm x 250 mm and height of 2000 mm, strengthened in the compressed area with a 35 mm layer of self-compacting concrete. Connector screws were used as interaction reinforcement. The main variables were the connectors' position and steel rate. Strengthened columns showed an increase in rupture by approximately three times load due to the increase of connectors' rate. One of the problems detected was the concrete reinforcement layer spalling near the rupture load, whose solution requires further research. There was also a reduction in columns' horizontal displacements, caused by a decrease in ductility. These results show the effectiveness of the strengthening technique employed.